Psilocin, A Psychedelic Drug, Exerts Anticonvulsant Effects Against PTZ‐ and MES‐Induced Seizures in Mice via 5‐HT1A and CB1 Receptors: Involvement of Nitrergic, Opioidergic, and Kynurenine Pathways - Mohammad Balabandian; Mohammad Amin Manavi; Ali Lesani; Razieh Mohammad Jafari; Hamed Shafaroodi; Navid Heidari; Javad Mirnajafi‐Zadeh; Alireza Foroumadi; Arya Afrooghe; Ahmad Reza Dehpour (Pharmacology Research & Perspectives)
ABSTRACT Epilepsy, a chronic neurological disorder affecting around 65 million people globally, is characterized by recurrent, unprovoked epileptic seizures. Psilocin, the active metabolite of psilocybin, a well‐known psychedelic compound, has recently gained attention for its potential antidepressant and anxiolytic properties. This study aims to investigate the anticonvulsant effects of psilocin. The study utilizes behavioral seizure models and electrophysiological recordings in mice to assess the anticonvulsant efficacy of psilocin. The pentylenetetrazole (PTZ) test for clonic seizures and the maximal electroshock (MES) test for generalized tonic–clonic seizures are employed. Cortical electrical activity is monitored to provide insights into the compound's effects on neuronal activity. The involvement of kynurenine pathway, opioidergic and nitrergic systems, as well as cannabinoid receptors using agonist/antagonist paradigms. Western blotting was employed to evaluate the expression levels of key receptors and enzymes implicated in psilocin's anticonvulsant effects. The findings indicate a possible modulation of seizure activity by psilocin, with modest doses (3 mg/kg, i.p.) demonstrating potential anticonvulsant effects. Remarkably, the administration of 1‐MT, L‐NAME, naltrexone, sildenafil, and AM‐251 led to a diminishment of the anticonvulsant effects of psilocin, underscoring the involvement of the kynurenine pathway, nitrergic and opioidergic systems, cGMP, and the CB1 receptor in mediating the anticonvulsant effects of psilocin, respectively. Based on western blotting analysis, the upregulation of 5‐HT1A but not 5‐HT2A and the downregulation of IDO and CB1 expression following psilocin administration were observed. Acute administration of psilocin exerts anticonvulsant effects that might be mediated at least in part through the kynurenine pathway, opioidergic, serotonergic, and nitrergic systems.